0921 Non-alcoholic Fatty Liver Disease among Patients with Sleep Disorders: A Nationwide Study of Taiwan, 2000–2013. (27th April 2018) - Wei, Y; Wu, C; Lee, P; Chen, H; Lin, C; Lin, C
Abstract: Introduction: Nonalcoholic fatty liver disease (NAFLD) is rapidly becoming the most common cause of chronic liver disease. In smaller studies, sleep disorder has been previously associated with NAFLD. The aim of this study was to assess the independent associations of NAFLD among patients with sleep disorders using a nationwide population-based data. Methods: A population-based cohort design was conducted using Taiwan National Health Insurance Research Database from 2000 to 2013. We identified the patients with sleep disorders during 2000 to 2005. The equal number of patients without sleep disorders were randomly selected as the comparison cohort. These patients were followed from the index date to the date of NAFLD diagnosed, loss follow-up, or the end of 2013. Cox proportional hazards models were used to estimate the risk of NAFLD among patients with sleep disorders. Results: A total of 33, 045 patients with sleep disorders were identified. The incidence of NAFLD was 14 per 10000 person-years among patients with sleep disorders and 6.19 per 10000 person-years in comparison cohort. The crude and adjusted hazard ratio (AHR) of NAFLD in the sleep disorders cohort was 2.26 (95% confidence interval [CI] =1.92–2.67) and 1.78 (95% CI = 1.46–2.16). Other independent risk factors included male gender (AHR =1.31, CI= 1.12–1.54), age 40–59 years (AHR 1.49, CI= 1.21–1.82), and dyslipidemia (AHR 2.51, CI= 2.08–3.04). The cumulative incidence curves of sleep disorders cohort did not show the temporal relationship between event and effect, which might infer to "web of causation" instead of a ''causal chain". In subgroup analysis, patients with sleep apnea had an increased risk of NAFLD (AHR 2.24, 95% CI= 1.05–4.77) compared to the reference group, whereas the AHR was 1.77 (95% CI= 1.46–2.15) among patients without sleep apnea. Conclusion: NAFLD is associated with sleep disorders. Although the exact mechanism is unknown, this association is probably through a web of causation model. Support (If Any): nil.